ANALISIS PERUBAHAN LUASAN TERUMBU KARANG MENGGUNAKAN CITRA LANDSAT 8 DI PULAU MATAHORA, WAKATOBI - Amanda Chairunnisa; Ekayanti Puspita Cahyani; Viantika Maulida; Della Ayu Lestari; Taufik Ejaz Ahmad (Jurnal Teknologi Perikanan dan Kelautan, 2022)
Indonesia is a maritime country blessed with diversity and natural wealth that diverse and beautiful that Indonesia is dubbed as marine mega biodiversity. Coral reefs as one of the biodiversity in Indonesian waters. Coral reefs are one of the coastal ecosystems that have an important role in the fisheries and marine resources. Matahora Island is one of the islands located in the eastern part of Wanci Island, South Wangi-wangi District, Wakatobi Regency. This study aims to analyze the habitat and changes of coral reef area using the Lyzenga algorithm and unsupervised classification to map and identify shallow marine water objects on Matahora Island, Wakatobi Regency by utilizing remote sensing in the period from 2015, 2018, to 2021. The value of the results the accuracy test obtained from the three years is between 90-99%. Based on the accuracy value, it can be categorized as an almost perfect agreement on the suitability of kappa accuracy. The results of the identification carried out using the Lyzenga algorithm and unsupervised classification on Matahora Island, Wakatobi Regency, obtained 5 classes, namely deep sea, live coral reef, dead coral, seagrass, and sand.